A novel nonlinear mechanical oscillator and its application in vibration isolation and energy harvesting. (16th June 2021) - Yang, Tao; Cao, Qingjie; Hao, Zhifeng
Highlights: This paper originally proposed a novel high-order quasi-zero stiffness oscillator. The theoretical model is derived with considering the effect of electromagnetic transduction. Lower initial isolation and maximum harvested power frequencies than the corresponding system without auxiliary rigid links. The conclusion of enhancing performances hold in both stochastic and harmonic excitations. Abstract: The nonlinear design of a new vibration structure is an essential part of the development of vibration isolation and energy harvesting technologies, and is one of the most effective technical means to improve the efficiency of low-frequency excitation. Due to structural constraints, high-efficiency vibration isolation and energy harvesting from ultra-low frequency or low intensity excitation has been a theoretical bottleneck and technical challenge in this field. In this study, this paper firstly proposes the theory and method of vibration isolation and energy harvesting based on the high-order quasi-zero stiffness (HQZS) mechanism, which is expected to break through the above bottleneck. Secondly, a detailed study of the HQZS oscillator with electromagnetic transduction under both stochastic and harmonic excitations is emphasized. The HQZS oscillator can not only achieve arbitrarily small stiffness near the equilibrium position through geometrically nonlinear parameter design, but also achieve vibration isolation or high-energy interwell oscillation under ultra-low frequency or low intensity excitations. Finally, compared with quad-stable and quasi-zero stiffness (QZS) systems, the results show that the HQZS oscillator has better vibration isolation and energy harvesting performance for ultra-lower stochastic excitation intensity or harmonic excitation frequency. Also, the initial isolation frequencies and maximum harvested power frequencies of the HQZS oscillator are lower than that of the QZS oscillator. The results will not only help to deepen the understanding of HQZS systems, but also provide new theoretical support and technical approaches for vibration isolation and energy harvesting under ultra-low frequency or low intensity excitation.